Kepuasan Pasien terhadap Mutu Pelayanan Keperawatan di Bagian Rawat Jalan Rumah Sakit - Malihah Ramadhani Rum; Oci Etri Nursanty (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: Patient satisfaction in healthcare services is crucial as it reflects the quality of service provided by the institution. Knowing the level of patient satisfaction is very useful for related institutions to evaluate ongoing programs and identify areas needing improvement. The quality of hospital services consists of two aspects, meeting established quality standards and satisfying customer (patient) needs. Hospitals need to focus on providing services that prioritize customer satisfaction. To enhance the quality of healthcare services, it can begin with evaluating each element contributing to patient satisfaction. Objectives: The objective of this study is to assess the level of patient satisfaction in the Outpatient Department so that the hospital can conduct evaluations and improve services according to patient needs. Methods: This study is a quantitative research using a descriptive survey approach. The population in this study consists of patients in the outpatient department in September 2023, totaling 3,112 patients. The sample size was determined using Slovin's formula, and the calculated sample size for this study is 97 patients. Results: Patient satisfaction with tangibles was found 1% rated it as bad, 8% as poor, 30% as good, and 60% as excellent. Reliability was found that 2% rated it as bad, 9% as poor, 31% as good, and 58% as excellent. Responsiveness was found that 1% rated it as bad, 5% as poor, 32% as good, and 62% as excellent. Assurance was found that 1% rated it as bad, 5% as poor, 32% as good, and 62% as excellent. Empathy was found that 1% rated it as bad, 11% as poor, 30% as good, and 58% as excellent. Conclusion: Patient satisfaction regarding nursing care services rated as excellent in the Outpatient Department of Ali Sibroh Malisi Hospital, assessed across five dimensions-tangibles, reliability, responsiveness, assurance, and empathy-averages below 70%. This is significantly far from the minimum service standard set by the Ministry of Health, which is 95%.